2020
DOI: 10.1080/09687637.2020.1820450
|View full text |Cite
|
Sign up to set email alerts
|

Representation of adverse childhood experiences is associated with lower public stigma towards people who use drugs: an exploratory experimental study

Abstract: BackgroundStigmatising attitudes towards people who use drugs are pervasive amongst the public. We investigated whether public stigma was affected by presentation of a history of adversity, and how substance use was described. MethodsA cross-sectional online study using a convenience sample, with a randomised 2 x 2 x 2 factorial design. Participants read one of eight randomly presented vignettes that described a fictional case history of substance use. In each vignette the gender of the subject (male or female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 107 publications
1
9
1
Order By: Relevance
“…Strengthening efforts to educate wider society regarding opioid use and the complexity of treatment and recovery might be another way of preventing stigma from influencing patients' treatment decisions. For example, calling attention to the life stories of people with SUD may reduce stigmatizing public attitudes (Sumnall et al, 2020). This study's overall findings support an emerging notion in both research and clinical work that the dominant understanding of successful treatment outcomes is rigid, unrealistic, and potentially harmful.…”
Section: Should Discontinuation Of Treatment Be Considered a Failure?supporting
confidence: 64%
“…Strengthening efforts to educate wider society regarding opioid use and the complexity of treatment and recovery might be another way of preventing stigma from influencing patients' treatment decisions. For example, calling attention to the life stories of people with SUD may reduce stigmatizing public attitudes (Sumnall et al, 2020). This study's overall findings support an emerging notion in both research and clinical work that the dominant understanding of successful treatment outcomes is rigid, unrealistic, and potentially harmful.…”
Section: Should Discontinuation Of Treatment Be Considered a Failure?supporting
confidence: 64%
“…These types of approach may also face some additional challenges. Rather than particular behaviours or perceived characteristic leading to beliefs that out-groups are simply 'less than human', dehumanising attitudes may reflect automatic perceptions that out-groups deserve low social hierarchical status, with foundations in long-standing inter-group interactions, and individual and societal attitudes towards intersecting factors such as class, ethnicity, and gender (Haslam and Loughnan, 2014), and beliefs about the blame and controllability of substance use disorders, and the dangerousness of PWUD (Corrigan, Kuwabara and O'Shaughnessy, 2009;Sattler et al, 2017;Ashford, Brown and Curtis, 2018;Sumnall et al, 2021). Furthermore, in accordance with social dominance theory, those who dehumanise may not simply perceive others as threatening, but may value asserting power and support efforts to separate groups through the use of discriminatory policy and other prejudicial actions, and are therefore less likely to respond to humanising interventions (Pratto, Sidanius and Levin, 2006;Markowitz and Slovic, 2020).…”
Section: Insert Table II Here Discussionmentioning
confidence: 99%
“…Acknowledging these challenges, one approach to humanisation could be through addressing popular media representations of PWUD (Fraser et al, 2016;McGinty, Kennedy-Hendricks and Barry, 2019). PWUD are typically framed in popular media as dangerous, 'contaminated', and lacking human agency (Atkinson and Sumnall, 2018;Atkinson and Sumnall, 2021), but previous work has shown that manipulations such as sympathetic framing and the use of neutral and person first terminology is associated with reduced stigma (Goodyear, Haass-Koffler and Chavanne, 2018;Sumnall et al, 2021). This is an area that requires further research with respect to dehumanisation.…”
Section: Insert Table II Here Discussionmentioning
confidence: 99%
See 2 more Smart Citations